Single-dose treatment of uncomplicated gonorrhoea in males with minocycline. Issue 2 (April 1975) - Shahidullah, M
Abstract : Minocycline in a single 300 mg. oral dose was given to 103 men with uncomplicated gonorrhoea, of whom 85 were followed-up for at least 2 weeks. The cure rate in the 85 followed was 94.1 per cent. There were no side-effects. Thus minocycline could be considered as an effective and safe alternative to penicillin in the single-dose treatment of uncomplicated gonorrhoea in the male, but at the moment it is too expensive for routine use.